2020
DOI: 10.1071/cp20253
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-based discovery of genes and networks related to RSC3Q-mediated resistance to Soybean mosaic virus in soybean

Abstract: Soybean mosaic virus (SMV) is a worldwide disease of soybean (Glycine max (L.) Merr.) that can cause serious reduction in yield and seed quality. Soybean cv. Qihuang-1 is an important source of resistance to SMV in China, carrying a resistance gene (RSC3Q) against SMV strain SC3. In order to discover genes and networks regulated by RSC3Q-mediated resistance in Qihuang-1, we analysed transcriptome data of a pair of near-isogenic lines, R (RSC3Q) and S (rSC3Q), from the cross Qihuang-1 × Nannong 1138-2 (rSC3Q), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Conventional transcriptome analysis has been applied to the analysis of molecular regulatory networks of soybean resistance to SMV. Although the plant-pathogen interaction pathway, MAPK signaling pathway, and plant hormone signal transduction pathway have been showed to respond to SMV infection, this response was mainly due to the role of some individual genes in the pathways [35][36][37][38][39]. The WGCNA method can identify the relationship between module eigengenes and hub genes with sample traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional transcriptome analysis has been applied to the analysis of molecular regulatory networks of soybean resistance to SMV. Although the plant-pathogen interaction pathway, MAPK signaling pathway, and plant hormone signal transduction pathway have been showed to respond to SMV infection, this response was mainly due to the role of some individual genes in the pathways [35][36][37][38][39]. The WGCNA method can identify the relationship between module eigengenes and hub genes with sample traits.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome analysis revealed a downregulation of NBS-LRR family genes in the susceptible variety Hefeng25 when infected with SMV N1 [36]. Potential genes related to ABA, plant-pathogen interaction, and jasmonic acid (JA) pathways related to Rsc3Q-mediated resistance to SMV strain SC3 were identified via transcriptome analysis between the R (RSC3Q) and S (rSC3Q) lines from the cross Qihuang-1 (which carries the resistance gene RSC3Q) × Nannong1138-2 (which carries the susceptible gene rSC3Q) [37]. Transcriptome analysis of the response of the resistant variety Kefeng-1 to SMV strain SC18 and the susceptible variety NN1138-2 also revealed that several genes related to the ethylene (ETH), jasmonic acid (JA), and salicylic acid (SA) signaling pathways may be involved in the disease resistance to SC18 [38].…”
Section: Introductionmentioning
confidence: 99%
“… Yuan et al. (2020) used transcriptomic analysis of R and S isogenic lines developed from Qihuang-1 Nannong 1138-2 × Soybean cv.…”
Section: Progress Of Functional Genomics: Discovery Of Candidate Resi...mentioning
confidence: 99%
“…Recent advances in RNA-seq-based transcriptome sequencing have offered novel insights into the molecular mechanisms of disease resistance and identified possible candidate gene(s) conferring resistance against various viral diseases in grain legumes (Martin et al, 2016;Dasgupta et al, 2021). Yuan et al (2020) used transcriptomic analysis of R and S isogenic lines developed from Qihuang-1 Nannong 1138-2 × Soybean cv. Qihuang-1 subjected to SMV infection at 6, 20, and 48 h post-inoculation (hpi) to elucidate the underlying candidate gene(s) conferring SMV resistance.…”
Section: Progress Of Functional Genomics: Discovery Of Candidate Resi...mentioning
confidence: 99%
“…Recently, (molecular) components of soybeans associated with biotic stress response have been identified ( Cooper et al, 2013 ; Delgado-Cerrone et al, 2018 ; Helm et al, 2019 ; Liu et al, 2015b ; Pottinger et al, 2020 ; Russell et al, 2015 ; Wei et al, 2020 ; Yuan et al, 2020 ). Thus, we felt it is necessary to fill the knowledge gap in a Korean soybean accession.…”
mentioning
confidence: 99%